Mewujudkan Keunggulan Kompetitif Berbasis Gusjigang Melalui Pengembangan Sentra Bisnis Budaya - Ita Rakhmawati; Widia Faridatul Mukaromah; Erina Musfiatul Rohmah (Departement of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri K.H Abdurrahman Wahid Pekalongan, 2021)
The purpose of this study is to analyze how to realize a gusjigang based competitive advantage through the development of business and cultural centers as well as to analyze the supporting and inhibiting factors. This research data is primary data type with data collection is done through interviews. The results of this study indicate that efforts to develop business and cultural centers through the Jenang Gusjigang Museum have proven to be able to create competitive advantages for companies in the midst of similar business competition. The advantages of the jenang museum as a business and cultural center are not only on the economic side (marketable) but also able to present the social, educational and cultural side. The company's efforts in realizing competitive advantage are carried out through three aspects, which include creating quality products, superior human resources, and developing marketing networks through excellent service.